1929
DOI: 10.1021/ja01379a004
|View full text |Cite
|
Sign up to set email alerts
|

THE SOLUBILITIES OF LEAD PHOSPHATES1

Abstract: THE SOLUBILITIES OF LEAD PHOSPHATES 997 the theory of Bronsted of velocity of reactions catalyzed by strong electrolytes. It seems to be very difficult to find a thoroughly satisfactory explanation of the changes of the decomposition velocity of diacetone alcohol in various solutions of strong electrolytes. Philadelphia, Pennsylvania

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1933
1933
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…This revelation set forth a research mission on corrosion control strategies to inhibit Pb release into drinking water. One of many corrosion control strategies was the use of orthophosphates due to the low solubility of Pb phosphate (Hatch, 1941;Jowett and Price, 1932;Millet and Jowett, 1929;Moore and Smith, 1942). Coating the interior wall of Pb drinking-water pipes with Pb phosphates, including pyromorphite, reduces the release of Pb to human consumption (Hopwood et al, 2002).…”
Section: Physical-chemical Interactions Between Phosphate Pb and Comentioning
confidence: 99%
See 3 more Smart Citations
“…This revelation set forth a research mission on corrosion control strategies to inhibit Pb release into drinking water. One of many corrosion control strategies was the use of orthophosphates due to the low solubility of Pb phosphate (Hatch, 1941;Jowett and Price, 1932;Millet and Jowett, 1929;Moore and Smith, 1942). Coating the interior wall of Pb drinking-water pipes with Pb phosphates, including pyromorphite, reduces the release of Pb to human consumption (Hopwood et al, 2002).…”
Section: Physical-chemical Interactions Between Phosphate Pb and Comentioning
confidence: 99%
“…The geochemical stability of pyromorphite has been extensively examined with pivotal research (Baker, 1964;Jowett and Price, 1932;Millet and Jowett, 1929;Nriagu, 1973a) suggesting a solubility product (K sp ) as low as 10 -84.4 ; however, a K sp = 10 -25.05 is more appropriate for soil pH range of 3 to 7 (Lindsay, 1979;Scheckel and Ryan, 2002). Drawing upon the technologies of corrosion control in drinking water, pure mineralogical lab studies on the formation of pyromorphite refined the theories of Smyth (1848) (Akao et al, 1989;Belokoneva et al, 1982;Cox and Majda, 1980;Dai and Hughes, 1989;Inegbenebor et al, 1989;Robert and Lefaucheux, 1989).…”
Section: Physical-chemical Interactions Between Phosphate Pb and Comentioning
confidence: 99%
See 2 more Smart Citations
“…(1) Pb3(PO4)2: Millet & Jowett (1929) studied the Pb-phosphate equilibrium, and concluded that (2) PbCO3: Maxwell & Bischoff (1929) examined the solubility of PbCO3 in solutions approximating to plasma under physiological conditions. They concluded that the Pb2+ concentration would be 1 x 10-1M at saturation.…”
Section: Solubility Of Pb Saltsmentioning
confidence: 99%